Machine Learning Approaches for Detection of SQL Injection Attacks - Anwar, Ican (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2025)
This study addresses the escalating cybersecurity challenges posed by SQL injection attacks in web applications and databases. This study aims to explore and evaluate the effectiveness of machine learning techniques in detecting SQL injection attacks, providing insights into the current state of research. The research involves collecting a relevant dataset of normal and malicious SQL queries, training and testing machine learning models (Support Vector Machines, Deep Neural Networks, and Random Forest). The Deep Neural Networks model stand out with the highest accuracy 0.95 and recall 0.98, indicating its robust capability to correctly classify instances of SQL Injection Attacks. The study contributes valuable insights into the current landscape of machine learning applications for SQL injection detection, providing a foundation for further exploration and analysis in this critical cybersecurity domain.